Spirituality Influences Emotion Regulation During Grief Talk: The Moderating Role of Prolonged Grief Symptomatology - Lee, Sherman A. (Journal of religion and health, 2022)
A growing body of research demonstrates that religion greatly affects people’s adjustment to loss. However, little is known about the influence of religiosity on emotion regulation during grief. The present study attempts to fill this void in the literature by examining the predictive relationship between variables assessing facets of religiosity and emotion regulation during an interview about loss in a sample of bereaved adults. The results demonstrated that religiousness, spirituality, and negative religious coping were correlated with emotion reactivity following an interview. Spirituality’s influence was also found to be moderated by prolonged grief symptoms, as spirituality predicted more adaptive emotion regulation among those with low-to-mild levels of prolonged grief symptomatology, but not among participants with elevated prolonged grief disorder (PGD) symptoms. These findings support the beneficial effects of religion in bereavement adjustment as well as its limits.